A bZIP transcription factor, CaLMF, mediated light-regulated camptothecin biosynthesis in Camptotheca acuminata. (4th October 2018) - Chang, Chunhao; Liu, Zhiwen; Wang, Yanyan; Tang, Zhonghua; Yu, Fang
Abstract: Camptothecin (CPT) has powerful biological activities and its analogs, irinothecan and topothecan, are effective anti-cancer drugs for clinical therapy. Camptothecin was first isolated from Camptotheca acuminata and its low accumulation in planta limits drug supply in the market. Previous works have confirmed that many environmental factors and plant hormones/elicitors could regulate CPT biosynthesis, but only light irradiance has a negative effect on CPT production in C. acuminata . Although light irradiance has been identified as a negative CPT biosynthesis regulator in C. acuminata for many years, the mechanisms of this regulation are still unknown. In order to search possible signal components involved in the process of light-regulated CPT biosynthesis, coexpression analysis was carried out according to the transcriptome database of Camptotheca above-ground green tissues. From coexpression analysis, a light-responsive bZIP transcription factor, CaLMF (Light-Mediated CPT biosynthesis Factor), was identified and further investigations showed that overexpression of CaLMF down-regulated the expression of CPT biosynthesis genes and decreased the accumulation of CPT in leaves, while light-regulated expression of CPT biosynthesis genes and CPT production were abolished in CaLMF silencing leaves under shading treatment. Our results show that CaLMF is a significant light signaling component, which mediates light-regulated CPT biosynthesis in C. acuminata.